The presentation of metabolic dysfunction and the relationship with energy output in breast cancer survivors: a cross-sectional study. - HUSSEY, JULIETTE; KENNEDY, MICHAEL (My University, 2013)
Background Breast cancer prognosis can be adversely influenced by obesity, physical inactivity and metabolic dysfunction. Interventions aimed at improving surrogate markers of breast cancer risk such as insulin resistance may result in improved breast cancer outcomes. The design of such interventions may be improved through increased understanding of metabolic presentation in this cohort. This cross-sectional study aimed to characterise the metabolic profile of breast cancer survivors relative to abdominal obesity and insulin resistance. A secondary aim was to compare measures of energy output across these groups. Methods Sixty-nine women (mean (SD) age 53.43 (9.39) years) who had completed adjuvant chemotherapy and radiotherapy for breast cancer were recruited. All measures were completed during one assessment conducted 3.1 (1.0) years post diagnosis. Body composition was measured by bioimpedance analysis and waist circumference (WC). Fasting (12 hour) blood samples were drawn to measure lipid profile, glucose, insulin, glycosylated haemoglobin A1c (HBA1c) and C-reactive protein (CRP). Insulin resistance was estimated by the homeostatic model assessment index (HOMA-IR)). Energy output was evaluated by resting metabolic rate (RMR) measured by indirect calorimetry and physical activity measured by accelerometry. Characteristics were compared across four groups (1. WC <80 cm, not insulin resistant; 2. WC 80–87.9 cm, not insulin resistant; 3. WC >88 cm, not insulin resistant; 4. WC >80 cm, insulin resistant) using ANOVA (p < 0.05). Results Group 4 was characterised by significant disturbances in measures of glucose metabolism (glucose, insulin, HOMA-IR and HBA1c) and raised CRP compared to other groups. Group 4 also displayed evidence of dyslipidemia and higher body composition values compared to Groups 1 and 2. Both absolute and adjusted RMR were significantly higher in the Group 4 versus all other groups. Physical activity levels were similar for all groups. Conclusions The results from this study suggest that participants who were both centrally obese and insulin resistant showed evidence of dyslipidemia, low-grade inflammation and glucose dysregulation. Metabolic profiles of participants who were centrally obese only were not significantly different from lean participants. Consideration of baseline metabolic presentation may be useful when considering the therapeutic targets for future interventions in this cohort.
PUBLISHED
Keywords: Breast cancer; Cancer